2023
DOI: 10.1093/ecco-jcc/jjad009
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Tool for Guiding Infliximab Induction Dosing to Maximize Long-term Deep Remission in Children with Inflammatory Bowel Diseases

Abstract: Background and aims Adequate infliximab concentrations during induction treatment are predictive for deep remission (corticosteroid-free clinical and endoscopic remission) at six months in children with inflammatory bowel diseases (IBD). Under standard infliximab induction dosing, children often have low infliximab trough concentrations. Model-informed precision dosing (MIPD) (i.e., model-based therapeutic drug monitoring) is advocated as a promising infliximab dosing strategy. We aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…before the third infusion), an infliximab concentration between 8.3 and 13.5 mg/L predicts clinical remission in the early postinduction phase. 13 , 14 , 21 An infliximab concentration higher than 5–7 mg/L measured at week 14 (i.e. before the fourth infusion) not only predicts short-term biochemical or endoscopic remission but also a sustained effect that lasts until week 52.…”
Section: Discussionmentioning
confidence: 99%
“…before the third infusion), an infliximab concentration between 8.3 and 13.5 mg/L predicts clinical remission in the early postinduction phase. 13 , 14 , 21 An infliximab concentration higher than 5–7 mg/L measured at week 14 (i.e. before the fourth infusion) not only predicts short-term biochemical or endoscopic remission but also a sustained effect that lasts until week 52.…”
Section: Discussionmentioning
confidence: 99%
“…70 Similarly, a recent study involving children with IBD receiving standard infliximab induction dosing revealed that infliximab clearance at weeks 6 and 12 was predictive of deep remission. 71 An RCT from South Korea, encompassing 112 biologic-naive children with CD who responded to induction treatment with infliximab, demonstrated the superiority of proactive TDM over clinically based dosing in sustained corticosteroid-free clinical remission and endoscopic healing. 72 A retrospective single-center study assessing outcomes in pediatric patients receiving either infliximab or adalimumab before (pre-TDM; 72.2% received infliximab) and after the implementation of institutional guidelines for proactive TDM (post-TDM; 65.5% received infliximab) found that proactive TDM improved key clinical outcomes, including sustained clinical remission, the incidence of high ATI titer, and anti-TNF cessation related to ATI.…”
Section: Whom To Monitormentioning
confidence: 99%
“…Moreover, the predictive performance of both single- and multi-model approaches remained robust even in the absence of covariate data, as long as a single most recent TC (preferably at the point of care) of infliximab was provided. Kantasiripitak et al 71 also expanded their work to pediatric patients with IBD.…”
Section: Translating Laboratory Data Into Dosing Recommendationsmentioning
confidence: 99%
“…However, the implementation of such tools into the clinical use of biologicals has been limited, which may also reflect the sparse evidence for the role of TDM in this setting. There are examples especially in the therapy of inflammatory bowel disease and some other immune diseases where MIPD has been explored to guide personalization [20][21][22][23]. Also for a drug like alemtuzumab a PK/PD model was developed for patients treated for chronic lymphocytic leukaemia (CLL) [24].…”
Section: Model Informed Precision Dosingmentioning
confidence: 99%